The Prevalence of Failure-Based Depression Among Elite Athletes - Hammond, T.; Gialloreto, C.; Kubas, H.; Davis, H. (Clinical Journal of Sport Medicine, 2013)
Objective: To assess the prevalence of diagnosed failure-based depression and self-reported symptoms of depression within a sample of elite swimmers competing for positions on Canadian Olympic and World Championship teams.